Identification and development of pyrazolo[4, 3-c]pyridine carboxamides as Mycobacterium tuberculosis pantothenate synthetase inhibitors. (12th December 2016) - Amaroju, Suresh; Kalaga, Mahalakshmi Naidu; Srinivasarao, Singireddi; Napiórkowska, Agnieszka; Augustynowicz-Kopeć, Ewa; Murugesan, Sankaranarayanan; Chander, Subhash; Krishnan, Rangan; Chandra Sekhar, Kondapalli Venkata Gowri
Abstract : A novel series of pyrazolo[4, 3- c ]pyridine carboxamides were synthesized and characterized. The compounds were evaluated for their antitubercular activity and pantothenate synthetase enzyme inhibition study. Abstract : The purpose of this study was to prepare various 1-((1-(substituted)-1 H -1, 2, 3-triazol-4-yl)methyl)- N, 3-diphenyl-6, 7-dihydro-1 H -pyrazolo[4, 3- c ]pyridine-5(4 H )-carboxamides using click chemistry. The synthesized compounds were characterized using various analytical techniques like NMR spectroscopy, mass spectrometry, and elemental analysis and screened for in vitro antitubercular activity against Mycobacterium tuberculosis (MTB) H37Rv strain and two 'wild' strains Spec. 210 and Spec. 192 using a classical test-tube method of successive dilution in Youmans' modification of the Proskauer and Beck liquid medium and were evaluated for a MTB pantothenate synthetase (PS) inhibition study as well. The final analogues exhibited minimum inhibitory concentration ranging from 24.72 to >200 μM. Among the compounds, 1-((1-(4-methoxyphenyl)-1 H -1, 2, 3-triazol-4-yl)methyl)- N, 3-diphenyl-6, 7-dihydro-1 H -pyrazolo[4, 3- c ]pyridine-5(4 H )-carboxamide (7d ) was found to be the most active compound with IC50 1.01 ± 0.32 μM against MTB PS; it inhibited MTB with MIC 24.72 μM and it was non-cytotoxic at 50 μM in the RAW 267 cell line. Further, 7d was docked into the crystal structure of MTB PS to investigate its binding interaction pattern.